2015
DOI: 10.1111/are.12847
|View full text |Cite
|
Sign up to set email alerts
|

High density rearing of rohu,Labeo rohita(Hamilton) from spawn to fry in concrete tanks: effect of daily feed ration and soil base on fry growth and survival

Abstract: Rearing of rohu spawn to fry size was carried out at high density (2000 spawn m−2) in large concrete nursery tanks (10 m × 5 m × 1.2 m) to standardize the daily ration of supplementary feed and to assess the impact of soil base on the fry performance. In Set‐1, supplementary feed was provided at 100% (control), 75% and 50% of the daily ration that is commonly used in earthen carp nursery ponds and named as the three treatments T‐1, T‐2 and T‐3 respectively. Although in Set‐II, performance of fry were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…All the water quality parameters in T‐1 were within the suitable ranges, as reported earlier in carp nursery (Basavaraja & Antony, 1997; Das et al, 2016; Jena et al., 2005), which eliminated the cause of any water quality‐related stress to lower its fry growth. It also indicated inadequacy in dietary energy supplementation through plankton for the densely stocked fry in T‐1, attributed to starvation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…All the water quality parameters in T‐1 were within the suitable ranges, as reported earlier in carp nursery (Basavaraja & Antony, 1997; Das et al, 2016; Jena et al., 2005), which eliminated the cause of any water quality‐related stress to lower its fry growth. It also indicated inadequacy in dietary energy supplementation through plankton for the densely stocked fry in T‐1, attributed to starvation.…”
Section: Discussionsupporting
confidence: 77%
“…This caused an increase in the BCR and significant rise in the profit margin ( p < .05) in T‐2 (Table 3), attributed to the use of supplementary feed. The authors have earlier reported a BCR of 4.47 in rohu reared at 2000 spawn m‐3 with similar level of supplementary feeding in concrete nursery system (Das et al., 2016). Similarly, with aeration as additional input, T‐3 not only had better water quality prevalence, but also produced fry which were 31% higher by number and 44% higher by biomass than T‐2, while its fry size was similar to that of the later.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The usual daily ration of supplementary feed is provided at approximately 400% of initial spawn biomass (6 kg per million spawn) on day 1 and subsequently doubled and tripled on day 6 and day 11, respectively (Jena and Das, 2011). However, Das et al (2015) observed similar growth performance for fry fed at 75 and 100% of the above mentioned ration and recommended the former, thereby saving good amount of supplementary feed. Similar attempts have also been made over the years to modify use of various other inputs to refine the carp seed production technology (Jena et al, 1998;Das et al, 2015;Kamble et al, 2017).…”
mentioning
confidence: 63%
“…However, Das et al (2015) observed similar growth performance for fry fed at 75 and 100% of the above mentioned ration and recommended the former, thereby saving good amount of supplementary feed. Similar attempts have also been made over the years to modify use of various other inputs to refine the carp seed production technology (Jena et al, 1998;Das et al, 2015;Kamble et al, 2017). Apart from fertilisation and supplementary feeding, depth of water in nursery also plays a significant role on the growth performance of the fry.…”
mentioning
confidence: 63%